2021
DOI: 10.3390/antibiotics11010048
|View full text |Cite
|
Sign up to set email alerts
|

NDM Production as a Dominant Feature in Carbapenem-Resistant Enterobacteriaceae Isolates from a Tertiary Care Hospital

Abstract: The worldwide spread and increasing prevalence of carbapenem-resistant Enterobacteriaceae (CRE) is of utmost concern and a problem for public health. This resistance is mainly conferred by carbapenemase production. Such strains are a potential source of outbreaks in healthcare settings and are associated with high rates of morbidity and mortality. In this study, we aimed to determine the dominance of NDM-producing Enterobacteriaceae at a teaching hospital in Karachi. A total of 238 Enterobacteriaceae isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 21 publications
(30 reference statements)
3
9
1
Order By: Relevance
“…Additionally, about 44.4% of carbapenem-resistant Enterobacteriaceae isolates were found to carry the carbapenemase gene. The metallo-β-lactamase, bla NDM was the predominant carbapenemase gene detected in our study which is in agreement with other reports from Pakistan 52 Turkey 58 and United Kingdom. 59 Therefore, strains producing the bla NDM are spreading widely across the globe and posing series public health threats mainly because of their wider range of resistance to clinically available antibiotic 58 and the plasmid associated with bla NDM is capable of wide rearrangement, widespread horizontal transmission and flexibility among bacterial species.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, about 44.4% of carbapenem-resistant Enterobacteriaceae isolates were found to carry the carbapenemase gene. The metallo-β-lactamase, bla NDM was the predominant carbapenemase gene detected in our study which is in agreement with other reports from Pakistan 52 Turkey 58 and United Kingdom. 59 Therefore, strains producing the bla NDM are spreading widely across the globe and posing series public health threats mainly because of their wider range of resistance to clinically available antibiotic 58 and the plasmid associated with bla NDM is capable of wide rearrangement, widespread horizontal transmission and flexibility among bacterial species.…”
Section: Discussionsupporting
confidence: 93%
“…However, the prevalence of CPE in our study is lower than two previous reports from Ethiopia 12.12% 12 and 16.2%, 11 and much lower than report from Uganda 28.6%, 49 France 36.2%, 19 Germany 53.3% 50 and multicenter observational study from seven Latin American countries 20.8%. 51 From those CPE isolates Klebsiella pneumoniae was the major carbapenemase-producing isolate in our study and a similar magnitude was reported from Czech Republic, 48 Nepal, 4 Uganda 49 and Pakistan 52 . The fact that K. pneumonia is the major organism responsible for ESBL and carbapenemase production could be associated with its notorious ability to accumulate and transfer resistance determinants and this has made it a leading causative agent of hospital-acquired infections.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While the global data suggested the higher prevalence of K. pneumoniae , P. aeruginosa , E. coli and A. baumannii from Tanzania, Algeria, Nepal and Saudi Arabia [ 46 , 47 , 48 , 49 ], our study demonstrated 42.1% CR among Enterobacterales . This is higher than prevalences previously reported from Pakistan such as 21.84% [ 50 ], 25.5% [ 51 ], 9.6% [ 52 ] and 6.5% [ 45 ]. However, our results are in agreement with the global reports that CRE prevalence is at alarming rates, such as 65.0% from the USA [ 53 ], 42.6% from Cuba [ 54 ] and 34.3% from China [ 55 ].…”
Section: Discussioncontrasting
confidence: 63%
“…Gram-negative bacteria, especially those falling under the family Enterobacterales (eg, Escherichia, Klebsiella , and Enterobacter ) as well as pseudomonads and Acinetobacter serve as the potential pathogens in nosocomial and community-acquired infections in urinary and respiratory tracts, blood stream, intra-abdominal and surgical site infections. 1 , 2 Some of these Gram-negative bacilli are also included in ESKAPE—a group of six nosocomial pathogens ( Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa , and Enterobacter spp.) that are notorious for drug resistance and virulence.…”
Section: Introductionmentioning
confidence: 99%